Enabling [18F]-bicyclo[6.1.0]nonyne for oligonucleotide conjugation for positron emission tomography applications: [18F]-anti-microRNA-21 as an example1. Issue 48 (18th June 2015) - Li, Xiang-Guo; Roivainen, Anne; Bergman, Jörgen; Heinonen, Arttu; Bengel, Frank; Thum, Thomas; Knuuti, Juhani
<x xml:space="preserve">Abstract</x> Bicyclo[6.1.0]nonyne (BCN)-based inverse electron demand Diels–Alder (IEDDA) conjugation for 18F-labeling of oligonucleotides!